Isomorphism of Hotel Management Contract and Capital Expenditure - Prillona, Trilas; Birton, M. Nur A.; Hakim , Luqman (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose -The purpose of this study is to explore the power relationship between the hotel owner and operator in the hotel management contract and capital expenditure (FFE) and the contract has not fully fulfilled the management contract standards and the suitability of the objectives in improving the overall performance and value of the property.Methodology/approach-This research is qualtitative, where informan from discusses the cooperation contract for the management of a local hotel chain between PT TBA. Findings-The results show that hotel management contracts and capital expenditure in hotels, i.e. the power relationship between owners and operators, are influenced by the three types of isomorphism. Coercive isomorphism creates pressure to comply with regulations, mimetic isomorphism encourages owners to imitate successful practices, and normative isomorphism gives legitimacy to operators who have norms or standards in the hotel business. Capital expenditure and Return on Investment (ROI) analyzes are influenced by these three isomorphisms. Coercive isomorphism indicates pressure to fulfill regulations, mimetic isomorphism encourages owners to mimic successful investments from other Santika Hotels, and normative isomorphism gives legitimacy to capital expenditure that is in line with Santika Group Hotel standards.Novelty/value-The isomorphism of hotel management contracts and capital expenditure can be seen from how hotels adapt and develop new practices in the face of pressures from both external and internal environments.